Power, alliances, and redistribution : the politics of social protection for low-income earners in Argentina, 1943-2015 - Bossert, Carl Friedrich (Budrich Academic Press, 2021)
Latin America is considered to be the most unequal continent in the world. Paradoxically, the development of resource-intensive social systems has done little to change the social imbalance. The author traces this paradox using the example of Argentina, reveals the underlying conflicts of power and interests and presents successful strategies for implementing an integrative policy. As the first study of its kind, it systematically examines the long-term development of social security for low-wage earners in Argentina and analyzes the decisive political, social and economic influencing factors.